Investigation on the binding specificity of Agrocybe cylindracea galectin towards α(2, 6)-linked sialyllactose by molecular modeling and molecular dynamics simulations. Issue 9 (22nd November 2019) - Parasuraman, Ponnusamy; Selvin, Jeyasigamani F. A.; Gromiha, M. Michael; Fukui, Kazuhiko; Veluraja, Kasinadar
Abstract: Galectins are β-galactoside binding proteins that act as potential cancer biomarkers. Agrocybe cylindracea galectin (ACG) is a fungal galectin which recognizes specifically α(2, 3)-linked sialyllactose and play a pivotal role in biological recognition processes. This manuscript has presented the theoretical investigation on enhancing the binding specificity of ACG towards α(2, 6)-linked sialyllactose. In silico single point and double point mutations were carried out at the binding site amino acid residues of ACG to enhance its binding to α(2, 6)-linked sialyllactose, and the mutated protein-carbohydrate complexes were simulated for 30 ns durations. Analysis of the interaction patterns of the carbohydrate at the binding site of wild type and mutated lectins revealed that sialic acid contributed more to the binding when compared with other sugar units in the trisaccharide and enhanced the binding specificity of ACG towards α(2, 6)-linked sialyllactose. Graphical Abstract: Theoretical investigation on the glycan-binding specificity of Agrocybe cylindracea galectin towards α(2, 6)-linked sialyllactose.